Editorial - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Fernandes; Mancebo, Deise; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2013)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Deise Maria Fernandes Mendes, Deise Mancebo, Rita Maria Manso de Barros